Double-helical --> ladder structural transition in the B-DNA is induced by a loss of dispersion energy - Cerný, Jirí; Kabelác, Martin; Hobza, Pavel (Journal of the American Chemical Society, 2008)
The role of the dispersion energy and electrostatic energy on the geometry and stability of the B-DNA helix was investigated. Both molecular dynamics simulations with empirical force field and hybrid quantum mechanical/molecular mechanics molecular dynamics simulations, where the dispersion or electrostatics term is suppressed/increased, on the one hand and an ab initio minimization procedure on the other have shown that the lack of the dispersion term leads to an increase of the vertical separation of the bases as well as to a loss of helicity, thus resulting in a ladder-like structure. A decrease of the electrostatic term produces a separation of the DNA strands. The biological consequences of both electrostatic and dispersion forces in DNA are enormous, and without either of them, DNA would become unstable and unable to provide the storage and transfer of genetic information.
Keywords: Static Electricity; termodynamika; vodíková vazba; statická elektřina; Thermodynamics; konformace nukleové kyseliny; Models, Molecular; molekulární modely; Nucleic Acid Conformation; Hydrogen Bonding; DNA